Editorial: Thank You, Gordon Hodgson! - Robinson, M.P. (ARCTIC, 1989)
. after four years of dedicated and extremely creative service, Dr. Gordon Hodgson steps down as academic editor of Arctic and Information North. His tenure in this position has been notable in many ways and caps a career in government service and academic life that has touched hundreds of graduate students and aspiring Arctic authors. . In the trenchant editorials appearing over his by-line, Gordon Hodgson has written his thoughts on arctic sovereignty, the need for a Nobel prize for arctic socio-economic studies, the desirability of creating a circumpolar university and a comprehensive northern on-line library system capable of text retrieval and delivery. . Whatever the response, Arctic's reader's have come to expect the editorial airing of complex northern issues, and the editorial page will continue under the leadership of our new editor Dr. Karen McCullough. .